Aloisio Magalhães and the North American experience: design in practice and theory - Dias, Ana (Arcos Design, 2022)
This article seeks to present the North American scenario found by Aloisio Magalhães at the end of the 1950s, when he began a process of turning off painting for entry into the field of design. In the pragmatic action of American artists and immigrants welcomed in the country, Aloisio recognizes the possibility of a design built in the practical exercise but also in teaching and critical theory, seeing in that system the mode of production compatible with contemporaneity.